2012
DOI: 10.1108/00070701211252057
|View full text |Cite
|
Sign up to set email alerts
|

What drives Greek consumer preferences for cask wine?

Abstract: PurposeCask wine (bag‐in‐box, soft pack) has not received considerable attention in wine marketing research, but interest among winemakers and consumers has been increasing steadily. However, little is known about what drives consumer preferences for cask wine and, furthermore, what the profile of the cask wine consumer is. This study aims at filling this gap.Design/methodology/approachBased on a web‐based survey, the best‐worst scaling (BWS) method was applied to measure the importance of attributes that Gree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 17 publications
3
33
0
1
Order By: Relevance
“…Their results allowed them to rank certain attributes in order of importance, with the first of these being price, followed by quality, packaging, previous experience, grape variety, region of origin and, finally, brand. Similar results were found in the study by Chrysochou et al (2012).…”
Section: Introductionsupporting
confidence: 92%
See 1 more Smart Citation
“…Their results allowed them to rank certain attributes in order of importance, with the first of these being price, followed by quality, packaging, previous experience, grape variety, region of origin and, finally, brand. Similar results were found in the study by Chrysochou et al (2012).…”
Section: Introductionsupporting
confidence: 92%
“…Some authors such as Elliot and Barth (2012) and Jarvis et al (2010) defend the relative importance of design compared to other attributes. However, in general terms it can be argued that most of the studies have concluded that attributes related to the design of the wine bottle are less important in the purchasing decision than other extrinsic attributes (Lockshin et al, 2009;Mueller and Szolnoky 2010b;Chrysochou et al, 2012;Madureira and Nunes, 2013;Nunes et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Considering that millennials' preferences for wine are strongly influenced by marketing added-value campaigns [67], communication about environmental activities using social media has a greater impact than for the older cohort. This might be explained by the fact that the young generation is more curious and has grown up in a period where new wine aspects such as environmental sustainability issues have gained great importance when choosing a product [10].…”
Section: Resultsmentioning
confidence: 99%
“…In particular, the experimental design for cluster identification approached on the default division of the whole sample from 2 to 5 clusters in function of individual preferences scores. In our research, the decision to use the rescaled score for the cluster analysis was made as it facilitates the analysis and interpretation of the preferences of the single clusters, and the comparison between them [70]. The best segmentation was evaluated by analyzing the log-likelihood (LL) values and the related Bayesian Information Criterion (BIC) of each model [71,72].…”
Section: Methodsmentioning
confidence: 99%